A critical analysis of the name change of Louis Trichardt to Makhado with special reference to principles and procedures - Mudau, Nditsheni Silas (My University, 2009)
The purpose of this research was to investigate, analyze and examine the historical background of Louis Trichardt, the renaming process with special reference to principles and procedures outlined by the South Africans Geographical Names Council. The study demonstrates the importance of principles and procedures when renaming a place. Ignoring these principles and procedures as outlined by the South African Geographical Names Council results in unnecessary confrontations and expenditure as it has been the case with Louis Trichardt. The study also reveals that not abiding by the rules, results in the polarization of communities. It also demonstrates how places should be renamed, which names are recommended and who should be involved. In the end, recommendation were suggested for the smooth renaming of places. This will help in coming up with names that will be acceptable to all.
Thesis (M.A (African Languages)) --University of Limpopo, 2009
Keywords: Names change; Place naming; 910.014; Names, geographical